Transición saludable a la discapacidad de la persona adulta con lesión medular - Fernandez Moya, Monserrat (2020)
Spinal Cord Injury (SCI) represents a catastrophic event for the person who acquires this disability, during the adaptation process the person is exposed to various complications and sequelae derived from this condition. Complex phenomena require theory to understand and interpret the relationships between concepts. Objective: to present a theoretical derivation and propose a model on the theory of healthy transition to disability of the adult person with Spinal Cord Injury. Material and methods: a theoretical derivation was made using the methodology proposed by J. Fawcett. Results: adaptation of the mid-range theory of transitions in adults with disabilities due to spinal cord injury. Conclusions: the model can be useful to explain how people in the process of adaptation to disability due to Spinal Cord Injury achieve well-being and what are the factors that influence during the process.